In Colombia, it is all about institutions (2009)
This paper highlights the importance of institutions on development and as it particularly applies to Colombia. It provides some evidence that the institutional environment in which an economic activity takes place is an important determinant of growth. It suggests that countries with high levels of economic growth are characterized with by high levels of economic freedom and judicial efficiency, low levels of corruption, effective bureaucracy, and protected private property.